Emergence of mutagenic/carcinogenic heterocyclic amines in traditional Saudi chicken dishes prepared from local restaurants. (October 2019) - Alsohaimi, Ibrahim Hotan; Khan, Mohammad Rizwan; Ali, Hazim Mohammed; Azam, Mohammad
Abstract: In the current investigation, five most potential HAs (MeIQx, 4, 8-DiMeIQx, IQ, MeIQ and PhIP) were analyzed in traditional Saudi chicken dishes (shawaya, Ala Al-Faham, kebab, saleeg, mandi, kabsa and madhbi) prepared from local restaurants. The aims of the present study were to identify the presence of HAs in cooked chicken dishes, and to conclude how the levels and types of HAs could be affected by cooking methods and food ingredients. In control samples, HAs were found at higher levels ranged from not quantified to 33.72 ng/g. Nonetheless, in chicken dishes, the HAs (MeIQx, 4, 8-DiMeIQx and PhIP) amounts are varied at higher range and relatively detected at lower levels from not quantified to 16.35 ng/g, IQ and MeIQ were not identified in any of the studied chicken dishes except shawaya where found to be not quantified. The HAs reduction rates were obtained at higher values in all of the studied samples, among them mandi sample demonstrates the reduction rates higher than 70%, whereas saleeg sample shows the reduction rates almost 100% except PhIP ( 95%). The obtained outcomes have markedly showed that HAs occurrence in thermally processed chicken dishes is extremely affected from both cooking methods and addition of food ingredients. Graphical abstract: Image 1 Highlights: Five highly potential HAs were analyzed in traditional Saudi chicken dishes. Cooking methods and food ingredients influence on HAs formation in chicken dishes. HAs are varied at higher range and detected at lower levels in chicken dishes. HAs reduction rates were achieved from 70 to 100% in some samples. Epidemiologic studies to account for effect of ingredients on cancer risk from HAs.